2011
DOI: 10.1371/journal.pone.0025929
|View full text |Cite
|
Sign up to set email alerts
|

Testing Protein Leverage in Lean Humans: A Randomised Controlled Experimental Study

Abstract: A significant contributor to the rising rates of human obesity is an increase in energy intake. The ‘protein leverage hypothesis’ proposes that a dominant appetite for protein in conjunction with a decline in the ratio of protein to fat and carbohydrate in the diet drives excess energy intake and could therefore promote the development of obesity. Our aim was to test the ‘protein leverage hypothesis’ in lean humans by disguising the macronutrient composition of foods offered to subjects under ad libitum feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
153
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 52 publications
22
153
3
2
Order By: Relevance
“…The resulting intake array was thus a vertical line, with little variation on the protein axis compared with the axis for non-protein. This is very similar to the rule of compromise that has been observed in experimental studies of humans Gosby et al 2011), which appear to be an important contributory factor to the epidemic of obesity that has swept many countries in recent decades.…”
Section: Wildlife Conservationsupporting
confidence: 81%
“…The resulting intake array was thus a vertical line, with little variation on the protein axis compared with the axis for non-protein. This is very similar to the rule of compromise that has been observed in experimental studies of humans Gosby et al 2011), which appear to be an important contributory factor to the epidemic of obesity that has swept many countries in recent decades.…”
Section: Wildlife Conservationsupporting
confidence: 81%
“…The hypophagic effect of protein-free diets, and hyperphagic effect of very low protein and moderately low protein diets, in the current study are consistent with the 'protein leverage' hypothesis 2 , as well as previous studies on protein restriction in rats, mice and humans 1,[6][7][8][9]14,17,22 . Although the low protein-induced hyperphagia is associated with a central orexigenic drive 11,[15][16][17][18] , the peripheral signals that transmit information to central neural networks are poorly defined.…”
Section: Discussionsupporting
confidence: 91%
“…A corollary to this hypothesis is that a reduction in the dietary protein concentration would increase total energy intake, due to overconsumption of carbohydrates and fat, in an effort to meet protein requirements. Consistent with this, moderately protein deficient diets were found to produce hyperphagia in rodents [6][7][8][9] and in some 1,10,11 but not all human studies 12,13 , whereas, severe protein restriction below a certain threshold leads to a reduction in food intake in rodents 9,14 . However, little is known of the underlying mechanisms by which moderate protein deficiency elicits such behavioural and metabolic adaptations and promotes positive energy balance with consequent predisposition to obesity and other metabolic disorders.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Satiating effects of dietary protein, a reduced choice of foods, and an aversion against dietary fat in the absence of carbohydrates have all been attributed to better weight loss with high protein diets (Weickert et al, 2005). Lowering the percent protein of the diet from 15% to 10% increases total energy intake (Gosby et al, 2011), further indicating that a higher intake of dietary protein may help to reduce energy intake. In a recent review, it is concluded that dietary protein by acting on satiety and energy expenditure in negative energy balance may prevent weight cycling effects (Westerterp-Plantenga et al, 2012), indicating a beneficial role on weight regulation.…”
Section: Dietary Protein and Blood Glucose Regulationmentioning
confidence: 99%